Strategic Management of Digital Technology in Increasing Zakat Fundraising - Miftahal Anjarsabda Wira Buana; Moh. Ah Subhan ZA; Akmalur Rijal (Program Studi Ekonomi Syariah, Fakultas Ekonomi dan Bisnis Islam, Universitas Al Hikmah Indonesia, 2022)
Digital zakat technology can be a promotional activity for a zakat institution that uses digital media as a medium for its introduction to the community, one of which is by using the internet or social media as a place for promotion or advertising. During the current pandemic, everything is carried out online to prevent crowds and transmission of the virus. There are several ZIS institutions whose income has decreased and their fundraising has been hampered by the COVID-19 pandemic. This is also a driving factor in increasing the number of potential zakat, infaq and online alms carried out by the community, where in 2021 zakat donations have increased by 30%, reaching 6 trillion from 2015, previously which only reached 4.2 trillion. The method used in this research was descriptive qualitative method. This qualitative descriptive method was used to describe the strategic management of digital technology comprehensively to see strategies for increasing the potential of zakat in the Indonesian zakat institution. Based on the theory and facts in the field that fundraising through digital technology was very significant: Mobile banking application customers could easily give zakat, infaq, and alms and their waqf to those who need it, Based on Baznas data, as of 2020 the total ZISWAF funds collected was estimated at Rp12.5 trillion. An important role was that zakat must be popularized among millennials who were already on a fixed income. The image of the institution could be obtained if the public is familiar with our institution. How do we introduce our institution on social media, that is, if we convey information about the institution to the public. After that, there must be interaction between the institution and the community through Facebook social media. The purpose of Facebook social media-based fundraising was to be able to raise ZIS funds, collect muzakki, and improve the image of the institution, by influencing or reminding and making people aware through the content posted. This meant reminding the public to be aware that the assets they own are not entirely their own. This social media was also a tool for reporting ZIS Institution transactions so that muzakki feel satisfied and public trust was built because they knew in detail the assets handed over to the ZIS institution.